2020
DOI: 10.1002/14651858.cd011708.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid point of care test for detecting urogenital Chlamydia trachomatis infection in nonpregnant women and men at reproductive age

Abstract: Rapid point of care test for detecting urogenital Chlamydia trachomatis infection in nonpregnant women and men at reproductive age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Current NAATs take hours or a day or more for results ( 16 , 17 ). While some C. trachomatis diagnostic tests take only 15 to 30 min, they are based on immunoassays that have an unacceptably low sensitivity of 17% to 83% ( 17 , 18 ) and are not recommended for use by the WHO ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current NAATs take hours or a day or more for results ( 16 , 17 ). While some C. trachomatis diagnostic tests take only 15 to 30 min, they are based on immunoassays that have an unacceptably low sensitivity of 17% to 83% ( 17 , 18 ) and are not recommended for use by the WHO ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In additional comparative analyses, there were no significant differences in detection accuracy between 4 commonly used IC-RDTs (Table 5). In a previous meta-analysis, including 19 studies with 13,676 participants, the mean sensitivity of IC-RDTs for detecting urogenital infection was 48% 18 . In some studies performed with vaginal swabs or endocervical swabs, the sensitivity of IC-RDTs for the detection of C. trachomatis ranged from 11.6% to 41.2% 19–21 .…”
Section: Discussionmentioning
confidence: 96%
“…In a previous meta-analysis, including 19 studies with 13,676 participants, the mean sensitivity of IC-RDTs for detecting urogenital infection was 48%. 18 In some studies performed with vaginal swabs or endocervical swabs, the sensitivity of IC-RDTs for the detection of C. trachomatis ranged from 11.6% to 41.2%. [19][20][21] In the current study, the sensitivity of NAATs was similar to those reported in studies by Cheng et al 22 (99.6% in urine samples and 98.8% in cervical swab samples) and Marshall et al 23 (93.7%-100%).…”
Section: Discussionmentioning
confidence: 99%
“…But As rapid NAAT tests have recently come out with improved sensitivity, NAATs such as Gene Xpert have been recommended as rapid tests. However, rapid test are still not thought to be effective for diagnosing chlamydia in men of reproductive age and nonpregnant women because of a high false-negative rates [37].…”
Section: Rapid Testmentioning
confidence: 99%